Enhancing Early Childhood Character Education Through Role Modeling and Care: A Case Study at Tadika Al-Fikh Orchard Port Klang Malaysia - Nurhaliza, Nurhaliza; Zuliana, Zuliana; Qorib, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
Responsible and honest personality Mostly formed through early character education. The paradigm of character education that emphasizes affection and role model is one of the most effective approaches to instill moral values in children. This study aims to investigate how kindergarten educational institutions use care and role model to implement the concept of character education. The research methodology used is a qualitative approach that utilizes the process of recording, interviews, and observations at Tadika AlFikh Orchard Port Klang Malaysia. Early character education plays a crucial role in shaping responsible and honest personalities. An effective paradigm for character education involves fostering affection and providing positive role models, helping children internalize moral values through observation and imitation. This study aims to explore how kindergarten educational institutions implement character education by emphasizing care and role modeling as key strategies. The research employs a qualitative approach, utilizing interviews, observations, and documentation at Tadika Al-Fikh Orchard, Port Klang, Malaysia. The results of the study showed that role models from teachers and parents. Children tend to imitate the behavior they see from adult figures around them, especially in terms of honesty, responsibility, and concern for others. In addition, concern can also be developed through social activities and interactions that involve cooperation and empathy in the learning environment. However, there are several obstacles and constraints faced, including the lack of cooperation from mothers and fathers and the various characters of children.